PENGARUH LATIHAN DRIBBLING SAMBIL MELINGKAR TERHADAP KEMAMPUAN DRIBBLING PERMAINAN BOLA BASKET PADA TIM PUTRA SMAN 2 TUALANG - Dumarto, Livi Nopi; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This problem with research it still a lack of mastering tecniquesdribbling. In addition players are also often unable to control the ball on the dribble theball so often time regardless. This research was conducted to find out whether there isthe effect of exercise dribbling while circular against dribbling ability of basketballgames on men’s team SMAN 2 Tualang. Type research used is experiment and usingone preetest-posttest disign. Population is research in Men’s Team SMAN 2 Tualang isthe entire populations of 10 people. While the sample technique used is total sampling(saturated sample) where all the population is sampled. The sample in this studyamounted to 10 people of Men’s Team SMAN 2 Tualang. The instrument is done in thisresearch is a test of dribbling surrounding obstacles, which aims to meansure aplayer’s dribbling ability. After that, the data is processed with statistics, to testnormality test with lilifors on a significance level α (0.05). The hypothesis put forwardis the effect of dribbling exercise while circular against dribbling ability. based on theanalysis of statistical data, there were an average of 24.1 pree-test and average of 25.6test posttest, Based on the analysisof the test produces Tcount 5.76 and Ttable 1.812,meaning Tcount > Ttable. Thus, there is the effect of dribbling exercise while circularagainst dribbling ability of basketball games on a men’s team SMAN 2 Tualang.Keywords : Dribbling Exercise While Circular Against, Dribbling Ability.